Membangun modal sosial pada gabungan kelompok tani - Teguh Budi Trisnanto; Fitriani Fitriani; Cholid Fatih (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Sumber Makmur farmer’s association (Gapoktan) have been changed structurally due to village enlargement processes. Differences of opinion, interest conflict, truth and norm, the decreasing the participation and cooperation were regarded as threat to Gapoktan performance. This study aims to explore members of Gapoktan’s perspective toward social capital values. This article also explores social capital mechanism to realize Gapoktan good performance. This study conducted in Pekon Adiluwih, Adiluwih sub-district, Pringsewu District in 2013. Respondents were Gapoktan management board and members (33 person). Data collected by in-depth interviews. Qualitative description method used to analyze the data. Based on the discussion, the research concludes that: (1) the main social capital elements patch in Sumber Makmur farmer’s group are: identity (X1, X2, X3), vision and goal (X4, X5), truth (X6, X7), smash anxiety (X8, X9), dan openness (X10). Positive value of social capital is considered as intrinsic value which create bonds between Gapoktan members. Mechanism to built solidarity of member was developed by strengthen trust to every members, and uniting identity, cooperation, and openness in a synergetic networks.